Characteristics of Nitrate Sorption of Andisols: Karakteristik Erapan Nitrat pada Andisol - Hartono, Arief; Anwar, Syaiful; Masruroh (Jurnal Ilmu Tanah dan Lingkungan, 2021)
Excessive use of urea and livestock manure by farmers causes the accumulation of nitrate ions on agricultural soils. Knowledge of the ability of soil to absorb nitrate is very important in terms of nitrate movement in the soil profile. The objectives of this study was to reveal the ability of the soils to bind nitrate through sorption and to reveal the soil properties affect the nitrate sorption. Nitrate sorption data were obtained by saturating the soil with nitrate solutions at various concentrations, after previously saturating the soil with chloride ions. Nitrates in the supernatant solution were determined using a UV Spectrophotometer with a wavelength of 210 nm and 275 nm. Then, the data were analyzed using two equations, namely, Langmuir equation and Freundlich equation. The results showed that the nitrate sorptions were best simulated by the Freundlich equation. The value of the constant K Freundlich equation as index of nitrate sorption maximum had a positive correlation with the organic carbon (C), aluminium extracted by ammonium oxalate (Alo),  aluminium extracted by Dithonite-citrate-bicarbonate (Ald) and Alo+1/2Feo (Andic property). The results suggested that organic C, Alo, Ald, and Andic property could be considered to control nitrate sorption.